Nano anti-bonding master batch for MLCC (multilayer ceramic capacitor) base film as well as preparation method and application of nano anti-bonding master batch

By using nano-level anti-bonding masterbatch in the MLCC release film base film, and combining nano-silica modified with epoxy group graft and carboxy modified PET resin, the existing MLCC base film has solved the problems of high surface roughness and poor anti-bonding performance, achieving high flatness and excellent anti-bonding performance, meeting the technical needs of high capacitance value and miniaturization of MLCC.

CN119798938AActive Publication Date: 2025-04-11SHANTOU BEST SCI & TECH

Patent Information

Application Number
CN202510091316.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-11
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The existing MLCC release film has high surface roughness, poor anti-stick performance and poor heat resistance, making it difficult to meet the technical needs of high capacitance value and miniaturization of MLCC.

Method used

Using parts by weight, a nano-scale anti-bonding masterbatch including unmodified PET resin, carboxy modified PET resin, anti-bonding composition, dispersant and anti-oxidant was prepared. The nano-silica modified by epoxy group grafting and carboxy modified PET resin was combined to produce the MLCC base film produced by the prepared anti-bonding masterbatch with high surface flatness and good anti-bonding performance.

Benefits of technology

It realizes the low roughness and high flatness of the MLCC base film, excellent anti-stick performance, and can meet the technical needs of high capacitance and miniaturization of MLCC. At the same time, the partial dispersion in the system is good and the production cost is low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005251620580000081
    Figure BDA0005251620580000081
  • Figure BDA0005251620580000091
    Figure BDA0005251620580000091
  • Figure HDA0005251620590000011
    Figure HDA0005251620590000011
Patent Text Reader

Abstract

The invention discloses a nanoscale anti-sticking master batch for an MLCC base film, which is prepared from the following raw materials in parts by weight: 80 to 95 parts of unmodified PET (Polyethylene Terephthalate) resin, 2 to 10 parts of carboxyl modified PET resin, 1 to 10 parts of anti-sticking composition, 0.1 to 2 parts of dispersing agent and 0.1 to 3 parts of antioxidant. According to the anti-sticking master batch disclosed by the invention, the epoxy group grafted and modified nano silicon dioxide and the carboxyl modified PET resin are combined to act, so that an MLCC base film produced by the prepared anti-sticking master batch is high in surface flatness and good in anti-sticking performance. The carboxyl modified PET resin with the molecular weight of 9800 g / mol and the carboxyl number of 40-50 / mol is adopted, the viscosity of the obtained anti-sticking master batch is appropriate, and no adverse effect is caused to subsequent processing production. The roughness of the prepared MLCC base film can reach 15 nm or below, meanwhile, the anti-sticking performance is excellent, and the technical requirements for the high capacitance value and miniaturization of the MLCC can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of polyester composite materials, and in particular to a nano anti-adhesive masterbatch for MLCC base film and a preparation method and application thereof. Background Art

[0002] MLCC (Multilayer Ceramic Capacitor) is a capacitor with a large capacitance, which is widely used in smart phones, automotive electronics, wearable devices, 5G communication base stations and other fields. MLCC release film is an important material for producing MLCC. MLCC release film usually uses polyester film as the base film, and the MLCC release base film is obtained by adding micron-level anti-sticking particles to the polyester material. However, the base film obtained in this way has problems such as high surface roughness, poor anti-sticking performance, and poor heat resistance, which in turn affects the thickness and surface roughness of the ceramic sheet, making it difficult to meet the technical requirements of high capacitance and miniaturization of MLCC. Therefore, it is very important to develop an anti-sticking masterbatch for thin films that has low surface roughness and excellent flatness and anti-sticking performance.

[0003] Chinese invention patent CN118684916B discloses a high temperature resistant MLCC release film base film and its preparation method, using terephthalic acid, 2-(pyridin-3-yl) terephthalic acid, and ethylene glycol as raw materials for esterification-polycondensation reaction, the product reacts with 1,3-propane sultone to obtain zwitterionic resin particle powder, sodium montmorillonite suspension is added, and the base film is obtained by melt extrusion. The base film has a smooth surface, low roughness, and high temperature resistance, but the preparation process is cumbersome. Chinese invention patent CN118906611A discloses a base film used for MLCC release film and its preparation method, the special masterbatch is made of KH550 modified inorganic filler and semi-aromatic polyamide, the special masterbatch makes the film material have excellent mechanical properties and heat resistance, and also has low roughness, avoiding the risk of inorganic particle precipitation. However, the thickness of the multilayer composite film is relatively high and cannot meet the needs of miniaturization. Summary of the invention

[0004] In order to develop an anti-sticking masterbatch for a film with low surface roughness and excellent flatness and anti-sticking properties, the first aspect of the present invention provides a nano-scale anti-sticking masterbatch for an MLCC base film. The raw materials for the preparation include 80-95 parts of unmodified PET resin, 2-10 parts of carboxyl-modified PET resin, 1-10 parts of an anti-sticking composition, 0.1-2 parts of a dispersant, and 0.1-3 parts of an antioxidant, in parts by weight.

[0005] As a preferred embodiment, the raw materials include 89-92 parts of unmodified PET resin, 5-6 parts of carboxyl-modified PET resin, 2-5 parts of anti-sticking composition, 0.1-0.2 parts of dispersant, and 0.1-0.2 parts of antioxidant, by weight.

[0006] As a preferred embodiment, the average molecular weight of the carboxyl-modified PET resin is 5000-10000 g / mol, and the number of carboxyl groups is 40-50 / mol.

[0007] As a preferred embodiment, the average molecular weight of the carboxyl-modified PET resin is 9800 g / mol, and the number of carboxyl groups is 48 / mol.

[0008] The molecular weight of the carboxyl-modified PET resin used is 9800 g / mol, and the weight ratio of the carboxyl-modified PET resin to the anti-sticking composition is (2-10): (1-10). The viscosity of the obtained anti-sticking masterbatch is appropriate and has no adverse effect on subsequent processing and production. Because the carboxyl-modified PET resin with a molecular weight of 9800 g / mol and the anti-sticking composition are at the preferred weight ratio, the anti-sticking masterbatch obtained during processing has good film-forming properties and film flatness. When the preferred weight ratio is exceeded, the MLCC base film produced from the anti-sticking masterbatch has a larger roughness and a reduced anti-sticking property, which affects the practical application of the MLCC release base film.

[0009] As a preferred embodiment, the melting point of the carboxyl-modified PET resin is 180-220° C., and the acid value is 200-250 mgKOH / g.

[0010] As a preferred embodiment, the melting point of the carboxyl-modified PET resin is 200° C. and the acid value is 230 mgKOH / g.

[0011] As a preferred embodiment, the intrinsic viscosity of the unmodified PET resin is 0.6-0.9 dL / g.

[0012] As a preferred embodiment, the intrinsic viscosity of the unmodified PET resin is 0.675 dL / g.

[0013] As a preferred embodiment, the anti-sticking composition is modified nano-silica, and the modified nano-silica is epoxy group-grafted nano-silica.

[0014] As a preferred embodiment, the particle size of the modified nano-silicon dioxide is 100-500 nm; the morphology of the modified nano-silicon dioxide is spherical.

[0015] As a preferred embodiment, the modified nano-silica is obtained by reacting silane with nano-silica, and the weight ratio of the silane to the nano-silica is (0.2-0.4): 1. Preferably, the weight ratio of the silane to the nano-silica is 0.2:1.

[0016] As a preferred embodiment, the silane is an epoxysilane, and the epoxysilane is selected from at least one of γ-glycidyloxypropyltriethoxysilane, γ-glycidyloxypropylmethyldiethoxysilane, and γ-glycidyloxypropyltrimethoxysilane.

[0017] As a preferred embodiment, the preparation method of the modified nano-silica comprises the following steps: dissolving epoxysilane in an ethanol aqueous solution, wherein the mass fraction of epoxysilane in the ethanol aqueous solution is 4%, then adding nano-silica, mixing evenly, stirring at 50°C for 2h, then filtering, and drying in a drying tank at 200°C for 1h to obtain modified nano-silica.

[0018] As a preferred embodiment, the volume ratio of ethanol to water in the ethanol aqueous solution is 8:2.

[0019] The MLCC base film produced by the anti-sticking masterbatch prepared by combining epoxy-grafted modified nano-silica with carboxyl-modified PET resin has high surface flatness and good anti-sticking performance. Because spherical silica is used as the main anti-sticking agent, the surface energy of nano-silica is high and it has hydrophilic hydroxyl groups, so it has poor dispersibility in polymers. By using propyl trimethoxy silane to graft the surface of silica, propyl trimethoxy silane reacts with the hydroxyl groups of silica, and epoxy groups are grafted to the surface of silica, which improves the problem of poor dispersibility of the hydrophilic groups of silica. The epoxy-grafted silica undergoes an ester exchange reaction with the terminal carboxyl groups of the carboxyl-modified PET resin. Since the number of carboxyl groups of the carboxyl-modified PET resin reaches 48 / mol, the epoxy-grafted silica can react with the terminal carboxyl groups of PET as much as possible, which increases the compatibility of nano-silica and PET, making silica highly dispersible in the PET system, and achieving the effect of low roughness and high flatness of the MLCC base film.

[0020] As a preferred embodiment, the antioxidant includes but is not limited to phenols, alcohol esters, and phosphate antioxidants. Preferably, the antioxidant is β-(3,5-di-tert-butyl 4-hydroxyphenyl) propionic acid octadecanol wax.

[0021] As a preferred embodiment, the dispersant includes but is not limited to wax dispersants, ethylene bisstearic acid amide, and pentaerythritol stearate.

[0022] As a preferred embodiment, the dispersant is polyethylene wax.

[0023] The first aspect of the present invention provides a method for preparing a nano-scale anti-sticking masterbatch for an MLCC base film, comprising the following steps:

[0024] S1 adds carboxyl modified PET resin into the extruder, heats it to 200-250℃, and melts and shears it;

[0025] S2: adding the anti-sticking composition, antioxidant and dispersant into the extruder at the front end side feeding port of the extruder, and premixing them with the carboxyl modified PET resin by melting at 200-250° C.;

[0026] S3 adds the unmodified PET resin into the extruder at the front end side feeding port of the extruder, heats it to 270-280°C, melt-mixes it with the mixture of step S2, and then extrudes and granulates it through a twin-screw extruder to obtain a nano-scale anti-sticking masterbatch for MLCC base film.

[0027] The third aspect of the present invention provides an application of a nano-scale anti-sticking masterbatch for an MLCC base film, which is applied in the preparation of an MLCC base film.

[0028] As a preferred embodiment, the preparation method of the MLCC base film comprises the following steps: PET resin and the prepared anti-sticking masterbatch are dropped into an extruder through a loss-in-weight scale, melt-filtered at a temperature of 250-300°C and then extruded from a die, cast on a cooling roller at a temperature of 30-35°C, preheated longitudinally at a preheating temperature of 70-75°C and stretched 3-4 times in the stretching section, cooled to 40-50°C in the cooling section, and then enters the transverse stretching preheating and transverse stretching box, the preheating temperature is 90-95°C, the transverse stretching temperature is 95-100°C, the stretching section is stretched 3-4 times, and then fixed in a heat setting section at a temperature of 210-220°C, cooled and rolled up to obtain the MLCC base film.

[0029] As a preferred embodiment, the preparation method of the MLCC base film comprises the following steps: PET resin and the prepared anti-sticking masterbatch are dropped into an extruder through a loss-in-weight scale, melt-filtered at a temperature of 280°C and then extruded from a die, cast on a cooling roller at a temperature of 30°C, preheated longitudinally at a preheating temperature of 70°C and stretched 3.5 times in the stretching section, then cooled to 50°C in a cooling section, and then enters a transverse stretching preheating and transverse stretching box with a preheating temperature of 90°C, a transverse stretching temperature of 100°C, and a stretching section stretching 3.5 times, and then set in a heat setting section at a temperature of 220°C, cooled and rolled up to obtain an MLCC base film.

[0030] As a preferred embodiment, the weight ratio of the PET resin to the prepared anti-sticking masterbatch is 7:(1-5).

[0031] As a preferred embodiment, the weight ratio of the PET resin to the prepared anti-sticking masterbatch is 7:3.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) The nano-scale anti-sticking masterbatch for the MLCC base film of the present invention is prepared by combining nano-silica modified by epoxy group grafting with carboxyl-modified PET resin. The MLCC base film produced by the anti-sticking masterbatch has high surface flatness and good anti-sticking performance.

[0034] (2) The nano-scale anti-sticking masterbatch for the MLCC base film of the present invention adopts a carboxyl-modified PET resin with a molecular weight of 9800 g / mol and a carboxyl group number of 40-50 / mol. The obtained anti-sticking masterbatch has a suitable viscosity and has no adverse effect on subsequent processing and production.

[0035] (3) The nano-scale anti-sticking masterbatch for the MLCC base film of the present invention has a characteristic viscosity of 0.639 dL / g, which is not significantly different from the traditional processing technology, does not require the introduction of new equipment for processing and production, and has a low production cost.

[0036] (4) The MLCC base film of the present invention uses a nano-scale anti-sticking masterbatch, and the roughness of the prepared MLCC base film can be less than 15nm, while having excellent anti-sticking performance, which can meet the technical requirements of high capacitance and miniaturization of MLCC.

[0037] (5) The nano-scale anti-sticking masterbatch for the MLCC base film of the present invention has good internal dispersibility and no obvious agglomeration phenomenon. The obtained anti-sticking masterbatch system is stable, has low haze, good dispersibility, and has low adhesion, thereby achieving an anti-sticking effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The dispersion of the nano-scale anti-sticking masterbatch for the MLCC base film prepared in Example 1 inside the slice was observed by electron microscopy.

[0039] Figure 2 The dispersion of the nano-scale anti-sticking masterbatch for the MLCC base film prepared in Example 2 inside the slice was observed by electron microscopy.

[0040] Figure 3 The dispersion of the nano-scale anti-adhesive masterbatch for the MLCC base film prepared in Comparative Example 1 inside the slice was observed by electron microscopy.

[0041] Figure 4 The dispersion of the nano-scale anti-sticking masterbatch for the MLCC base film prepared in Comparative Example 2 inside the slice was observed by electron microscopy.

[0042] Figure 5 The dispersion of the nano-scale anti-adhesive masterbatch for the MLCC base film prepared in Comparative Example 3 inside the slice was observed by electron microscopy. DETAILED DESCRIPTION

[0043] Example 1

[0044] A nano-scale anti-sticking masterbatch for MLCC base film, wherein the raw materials for preparation include 91.7 parts of unmodified PET resin, 6 parts of carboxyl-modified PET resin, 2 parts of anti-sticking composition, 0.1 parts of dispersant and 0.2 parts of antioxidant, in parts by weight.

[0045] The unmodified PET resin has an intrinsic viscosity of 0.675 dL / g and is purchased from Yizheng Chemical Fiber with a brand name of FG600.

[0046] The carboxyl-modified PET resin has an average molecular weight of 9800 g / mol, 48 carboxyl groups / mol, a melting point of 200° C., and an acid value of 230 mgKOH / g. It was purchased from Wuhan Hyperbranched Resin Technology Co., Ltd., with a brand name of C304.

[0047] The anti-sticking composition is modified nano silicon dioxide.

[0048] The preparation method of modified nano silicon dioxide comprises the following steps: dissolving epoxysilane in an ethanol aqueous solution, wherein the mass fraction of epoxysilane in the ethanol aqueous solution is 4%, then adding nano silicon dioxide, mixing evenly, stirring at 50°C for 2h, then filtering, and drying in a drying pot at 200°C for 1h to obtain modified nano silicon dioxide.

[0049] The epoxy silane is γ-glycidyloxypropyltriethoxysilane, and the weight ratio of the silane to the nano-silicon dioxide is 0.5:1.

[0050] The nano-silicon dioxide has a particle size of 500 nm and a spherical shape and is purchased from Dongguan Xinweijin Industrial Co., Ltd. with a brand number of XWJ-SQNM80500.

[0051] The volume ratio of ethanol to water in the ethanol aqueous solution is 8:2.

[0052] The antioxidant is β-(3,5-di-tert-butyl 4-hydroxyphenyl) propionic acid octadecanol wax.

[0053] The dispersant polyethylene wax is purchased from Clariant, brand E.

[0054] A method for preparing a nano-scale anti-bonding masterbatch for an MLCC base film comprises the following steps:

[0055] S1 adds carboxyl modified PET resin into the extruder, heats it to 240°C, and melts and shears it;

[0056] S2: adding the anti-sticking composition, antioxidant and dispersant into the extruder at the front end side feeding port of the extruder, and premixing them with the carboxyl modified PET resin by melting at 200-250° C.;

[0057] S3 adds the unmodified PET resin into the extruder at the front end side feeding port of the extruder, heats up to 275° C., melts and mixes with the mixture of step S2, and then extrude and granulate through a twin-screw extruder to obtain a nano-scale anti-sticking masterbatch for MLCC base film.

[0058] The prepared anti-adhesive masterbatch has a dispersibility electron microscopy image. Figure 1 .

[0059] Example 2

[0060] A nano-scale anti-sticking masterbatch for MLCC base film, wherein the raw materials for preparation include 89.7 parts of unmodified PET resin, 5 parts of carboxyl-modified PET resin, 5 parts of anti-sticking composition, 0.1 parts of dispersant and 0.2 parts of antioxidant, in parts by weight.

[0061] The rest of the implementation is the same as Example 1.

[0062] The prepared anti-adhesive masterbatch has a dispersibility electron microscopy image. Figure 2 .

[0063] Comparative Example 1

[0064] A nano-scale anti-sticking masterbatch for MLCC base film, wherein the raw materials for preparation include 97.6 parts of unmodified PET resin, 0 parts of carboxyl-modified PET resin, 2 parts of anti-sticking composition, 0.2 parts of dispersant and 0.2 parts of antioxidant, in parts by weight.

[0065] The rest of the implementation is the same as Example 1.

[0066] The prepared anti-adhesive masterbatch has a dispersibility electron microscopy image. Figure 3 .

[0067] Comparative Example 2

[0068] A nano-scale anti-sticking masterbatch for MLCC base film, wherein the raw materials for preparation include 94.7 parts of unmodified PET resin, 0 parts of carboxyl-modified PET resin, 5 parts of anti-sticking composition, 0.1 parts of dispersant and 0.2 parts of antioxidant, in parts by weight.

[0069] The anti-sticking composition is modified silica.

[0070] The silicon dioxide has a particle size of 3 μm and an irregular morphology and is purchased from Guangzhou Shenna Trading Co., Ltd. with a brand number of K720.

[0071] The rest of the implementation is the same as Example 1.

[0072] The prepared anti-adhesive masterbatch has a dispersibility electron microscopy image. Figure 4 .

[0073] Comparative Example 3

[0074] A nano-scale anti-sticking masterbatch for MLCC base film, wherein the raw materials for preparation include 89.7 parts of unmodified PET resin, 5 parts of carboxyl-modified PET resin, 5 parts of inorganic composition, 0.1 parts of dispersant and 0.2 parts of antioxidant, in parts by weight.

[0075] The inorganic composition is nano silicon dioxide.

[0076] The nano-silicon dioxide has a particle size of 500 nm and a spherical shape and is purchased from Foshan Oulite New Material Technology Co., Ltd. with a brand number of L500.

[0077] The prepared anti-adhesive masterbatch has a dispersibility electron microscopy image. Figure 5 .

[0078] Performance Testing

[0079] 1. Viscosity: The viscosity was measured using the IVS300 automatic Ubbelohde viscosity measurement system in accordance with GB / T 14190-2017. The test results are shown in Table 1.

[0080] Table 1

[0081] Viscosity (dL / g) Example 1 0.639 Example 2 0.600 Comparative Example 1 0.626 Comparative Example 2 0.608 Comparative Example 3 0.612

[0082] Application Example 1

[0083] The MLCC base film prepared in Example 1 is prepared into an MLCC base film using a nano-scale anti-sticking masterbatch. The preparation method of the MLCC base film comprises the following steps: PET resin and the prepared anti-sticking masterbatch are dropped into an extruder through a loss-in-weight scale, melt-filtered at a temperature of 280°C and then extruded from a die, cast on a cooling roller at a temperature of 30°C, preheated longitudinally at a preheating temperature of 70°C and stretched 3.5 times in a stretching section, then cooled to 50°C in a cooling section, and then enters a transverse stretching preheating and transverse stretching box with a preheating temperature of 90°C, a transverse stretching temperature of 100°C, and a stretching section with a stretching temperature of 3.5 times, and then set in a heat setting section at a temperature of 220°C, cooled and rolled up to obtain an MLCC base film.

[0084] The weight ratio of the PET resin to the prepared anti-bonding masterbatch is 7:3. The PET resin is purchased from Yizheng Chemical Fiber, with a brand name of FG600.

[0085] Application Example 2

[0086] The MLCC base film prepared in Example 2 is prepared into an MLCC base film using a nano-scale anti-sticking masterbatch, and the rest of the implementation methods are the same as those in Application Example 1.

[0087] Application Comparative Example 1

[0088] The MLCC base film prepared in Comparative Example 1 is prepared into an MLCC base film using a nano-scale anti-sticking masterbatch, and the rest of the implementation methods are the same as those in Application Example 1.

[0089] Application Comparative Example 2

[0090] The MLCC base film prepared in Comparative Example 2 is prepared into an MLCC base film using a nano-scale anti-sticking masterbatch, and the rest of the implementation methods are the same as those in Application Example 1.

[0091] Application Comparative Example 3

[0092] The MLCC base film prepared in Comparative Example 3 is prepared into an MLCC base film using a nano-scale anti-sticking masterbatch, and the rest of the implementation methods are the same as those in Application Example 1.

[0093] Performance Testing

[0094] 2. Haze: Haze is measured according to standard GB / T 2410-2008.

[0095] 3. Adhesion: The adhesion tester MODEL D9047 was used to measure the adhesion according to ATSM D 3354-2015 standard. The adhesion between the MLCC substrates treated with corona (corona vs corona) and between the MLCC substrates treated with corona and the MLCC substrates not treated with corona (corona vs non-corona) were tested respectively.

[0096] 4. Roughness (Ra measurement): The surface roughness was measured using a surface roughness measuring machine SE3500 manufactured by Kosaka Laboratory Co., Ltd. in accordance with JIS B0601-1994.

[0097] The test results are shown in Table 2.

[0098] Table 2

[0099]

[0100]

Claims

1. A nano-scale anti-sticking masterbatch for MLCC base film, characterized in that: The raw materials include 80-95 parts of unmodified PET resin, 2-10 parts of carboxyl-modified PET resin, 1-10 parts of anti-sticking composition, 0.1-2 parts of dispersant and 0.1-3 parts of antioxidant in parts by weight.

2. The nano-scale anti-bonding masterbatch for MLCC base film according to claim 1, characterized in that: The average molecular weight of the carboxyl-modified PET resin is 5000-10000 g / mol, and the number of carboxyl groups is 40-50 / mol.

3. The nano-scale anti-sticking masterbatch for MLCC base film according to claim 1, characterized in that: The carboxyl-modified PET resin has a melting point of 180-220° C. and an acid value of 200-250 mgKOH / g.

4. The nano-scale anti-sticking masterbatch for MLCC base film according to claim 1, characterized in that: The intrinsic viscosity of the unmodified PET resin is 0.6-0.9 dL / g.

5. The nano-scale anti-sticking masterbatch for MLCC base film according to claim 1, characterized in that: The anti-sticking composition is modified nano-silicon dioxide, and the modified nano-silicon dioxide is epoxy group-grafted nano-silicon dioxide.

6. The nano-scale anti-sticking masterbatch for MLCC base film according to claim 1, characterized in that: The anti-sticking composition is modified nano-silicon dioxide, which is obtained by the reaction of silane and nano-silicon dioxide, and the weight ratio of the silane to the nano-silicon dioxide is (0.2-0.4):

1.

7. The nano-scale anti-sticking masterbatch for MLCC base film according to claim 6, characterized in that: The particle size of the nano silicon dioxide is 100-500nm; the morphology of the nano silicon dioxide is spherical.

8. The nano-scale anti-sticking masterbatch for MLCC base film according to claim 6, characterized in that: The silane is an epoxy silane, and the epoxy silane is selected from at least one of γ-glycidyloxypropyl triethoxy silane, γ-glycidyloxypropyl methyl diethoxy silane, and γ-glycidyloxypropyl trimethoxy silane.

9. A method for preparing the nano-scale anti-sticking masterbatch for MLCC base film according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1 adds carboxyl modified PET resin into the extruder, heats it to 200-250℃, and melts and shears it; S2: adding the anti-sticking composition, antioxidant and dispersant into the extruder at the front end side feeding port of the extruder, and premixing them with the carboxyl modified PET resin by melting at 200-250° C.; S3 adds the unmodified PET resin into the extruder at the front end side feeding port of the extruder, heats it to 270-280°C, melt-mixes it with the mixture of step S2, and then extrudes and granulates it through a twin-screw extruder to obtain a nano-scale anti-sticking masterbatch for MLCC base film.

10. An application of the nano-scale anti-sticking masterbatch for MLCC base film according to any one of claims 1 to 8, characterized in that: Used in the preparation of MLCC base film.

Citation Information

Patent Citations

  • Anti-adhesion master batch, preparation method and preparation method of release film base film

    CN109880311A

  • Low-floating-fiber polyformaldehyde material as well as preparation method and application thereof

    CN114276647A

  • Preparation method of solvent-free self-emulsifying water-soluble chlorinated polypropylene

    CN115505128A

  • Anti-bonding master batch for release base film of multilayer chip ceramic capacitor and preparation process of anti-bonding master batch

    CN117285806A

  • Polybutylene terephthalate composition as well as preparation method and application thereof

    CN117700950A

Cited By

  • High-gloss low-haze polyester masterbatch, preparation method and application thereof

    CN122521094A

  • High-gloss low-haze polyester masterbatch, preparation method and application thereof

    CN122521094B